The wonder of heat energy; a picture story of the vital part heat plays in our world. - Ruchlis, Hyman; Hirsh, Alice, active 1957- (New York: Harper, 1961)
Discusses the importance of heat in our everyday life, the role of heat in shaping the earth and influencing weather, and the sources of heat.
Keywords: Heat -- Juvenile literature; Heat